Long‐term continental changes in wing length, but not bill length, of a long‐distance migratory shorebird. Issue 9 (4th April 2017) - Lank, David B.; Xu, Cailin; Harrington, Brian A.; Morrison, Richard I. Guy; Gratto‐Trevor, Cheri L.; Hicklin, Peter W.; Sandercock, Brett K.; Smith, Paul Allen; Kwon, Eunbi; Rausch, Jennie; Pirie Dominix, Lisa D.; Hamilton, Diana J.; et al.
Abstract: We compiled a >50‐year record of morphometrics for semipalmated sandpipers ( Calidris pusilla ), a shorebird species with a Nearctic breeding distribution and intercontinental migration to South America. Our data included >57, 000 individuals captured 1972–2015 at five breeding locations and three major stopover sites, plus 139 museum specimens collected in earlier decades. Wing length increased by ca. 1.5 mm (>1%) prior to 1980, followed by a decrease of 3.85 mm (nearly 4%) over the subsequent 35 years. This can account for previously reported changes in metrics at a migratory stopover site from 1985 to 2006. Wing length decreased at a rate of 1, 098 darwins, or 0.176 haldanes, within the ranges of other field studies of phenotypic change. Bill length, in contrast, showed no consistent change over the full period of our study. Decreased body size as a universal response of animal populations to climate warming, and several other potential mechanisms, are unable to account for the increasing and decreasing wing length pattern observed. We propose that the post‐WWII near‐extirpation of falcon populations and their post‐1973 recovery driven by the widespread use and subsequent limitation on DDT in North America selected initially for greater flight efficiency and latterly for greater agility. This predation danger hypothesis accounts for many features of the morphometric data and deserves further investigation in this and other species. Abstract : Wing lengths of a small shorebird lengthened during a period when avian predators were rare due to extensive use of DDT and have shortened since DDT's widespread banning in North America. The change is wing‐specific, rather than being associated with general body size change. We suggest that a less dangerous world favored birds with longer wings better adapted to long‐distance flight, while a more dangerous world favored more agile birds with shorter wings.